TINJAUAN YURIDIS TERHADAP PERTANGGUNGJAWABAN KORPORASI DALAM TINDAK PIDANA KORUPSI - Andi Wijaya; Erdianto '; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
Demand accountability for the corporate corruption in Indonesia still agree and who disagree. Groups for the corporation considers it is time to be held accountable in criminal acts of corruption and to counter the group considers asking corporate responsibility in the crime of corruption is something that is contradictory because the corporation does not have mensrea like humans. Regardless of the debate agree and do not agree that, of several criminal offenses outside the Penal Code including Law No. 31 by 1999 in junto the Law No. 20 by 2001 on Eradication of Corruption is not very effective in practice settings.The purpose of this study, to determine the setting of corporate responsibility in the crime of corruption is based on Law No.31 by 1999 in junto the Law No.20 by 2001 on Eradication of Corruption and to determine the cause of corporate criminal liability is difficult to apply under the Law No.31 by 1999 junto Law 20 by 2001 on the Eradication of Corruption.The setting corporate criminal liability in corruption in Article 20 paragraph (1) pursuant to Act No. 31 by 1999 in junto the Law No. 20 by 2001 on Eradication of Corruption has not effectively implemented, the problems that corporate responsibility can not be applied in a criminal act corruption as contained in Law No. 31 by 1999 in junto the Law No. 20 by 2001 on Eradication of Corruption because first, the debate on the principle of non potest, second, delinguere university, the contents of the provision sof Article 20 paragraph (1), paragraph (3) and paragraph (4) of Law No.31 by 1999 Junto Law No. 20 by 2001 on Eradication of Corruption is difficult to be fulfilled due to circumstances and the conditions contained in the law corruption is very difficult to materialize. First, advice, Revision Act No. 31 of 1999 Jo Law Number 20 Year 2001 on Eradication of Corruption second, the application of criminal punishment in thecorporatecorruptionwas time considered humanist values and well-being as a form of existence and efficiency of a law.